Hubungan antara Harga Diri dan Prestasi Akademik dengan Subjective Well Being pada Mahasiswa Jurusan Akuntansi Fakultas Ekonomi dan Bisnis di Universitas Persada Indonesia Y.A.I - Andini, Purti; Maryatmi, Anastasia Sri (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This research is a quantitative study that aims to examine the relationship between self-esteem and subjective well being, the relationship between academic achievement and subjective well being, and the relationship between self-esteem and academic achievement with subjective well being. The subjects in this study were late adolescents who were students of the Department of Accounting, Faculty of Economics and Business 2018 at the University of Persada Indonesia Y.A.I. This research used saturated sampling technique, and got respondents as many as 85 people. This study used 2 scales of measuring instruments and documentation, namely: a scale of measuring self-esteem and a scale of measuring subjective well being, as well as documentation of the respondent’s grade-point average. The results of this study resulted in a significant relationship between self-esteem and subjective well being in a positive direction with a correlation of r = 0.450 and p <0.05, while there was no relationship between academic achievement and subjective well being with r = -0.073 and p> 0.05.